Metabolomic analysis reveals altered skeletal muscle amino acid and fatty acid handling in obese humans. (10th April 2015) - Baker, Peter R.; Boyle, Kristen E.; Koves, Timothy R.; Ilkayeva, Olga R.; Muoio, Deborah M.; Houmard, Joseph A.; Friedman, Jacob E.
<x xml:space="preserve">Abstract</x> Objective Investigate the effects of obesity and high‐fat diet (HFD) exposure on fatty acid oxidation and TCA cycle intermediates and amino acids in skeletal muscle to better characterize energy metabolism. Methods Plasma and skeletal muscle metabolomic profiles were measured from lean and obese males before and after a 5‐day HFD in the 4 h postprandial condition. Results At both time points, plasma short‐chain acylcarnitine species (SCAC) were higher in the obese subjects, while the amino acids glycine, histidine, methionine, and citrulline were lower in skeletal muscle of obese subjects. Skeletal muscle medium‐chain acylcarnitines (MCAC) C6, C8, C10:2, C10:1, C10, and C12:1 increased in obese subjects, but decreased in lean subjects, from pre‐ to post‐HFD. Plasma content of C10:1 was also decreased in the lean but increased in the obese subjects from pre‐ to post‐HFD. CD36 increased from pre‐ to post‐HFD in obese but not lean subjects. Conclusions Lower skeletal muscle amino acid content and accumulation of plasma SCAC in obese subjects could reflect increased anaplerosis for TCA cycle intermediates, while accumulation of MCAC suggests limitations in β‐oxidation. These measures may be important markers of or contributors to dysregulated metabolism observed in skeletal muscle of obese humans.